2023
DOI: 10.3390/biom13010106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Caffeine Consumption on Synaptic Function, Metabolism and Adenosine Modulation in Different Brain Areas

Abstract: Adenosine receptors mainly control synaptic function, and excessive activation of adenosine receptors may worsen the onset of many neurological disorders. Accordingly, the regular intake of moderate doses of caffeine antagonizes adenosine receptors and affords robust neuroprotection. Although caffeine intake alters brain functional connectivity and multi-omics analyses indicate that caffeine intake modifies synaptic and metabolic processes, it is unclear how caffeine intake affects behavior, synaptic plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…first provided evidence that adenosine release is activity-dependent (Mitchell, Lupica et al 1993). A recent study in hippocampus showed that endogenous adenosine within excitatory synapses can very from 8-60 µM under basic (0.1 Hz) to high frequency (100 Hz) stimulation (Lopes, Goncalves et al 2023). These values are much higher than the previously reported levels of extrasynaptic adenosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…first provided evidence that adenosine release is activity-dependent (Mitchell, Lupica et al 1993). A recent study in hippocampus showed that endogenous adenosine within excitatory synapses can very from 8-60 µM under basic (0.1 Hz) to high frequency (100 Hz) stimulation (Lopes, Goncalves et al 2023). These values are much higher than the previously reported levels of extrasynaptic adenosine.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent research has revealed that adenosine also plays a pivotal role in augmenting excitatory synaptic transmission via acting A 2A ARs across many brain regions (Cunha and Ribeiro 2000, Ciruela, Casado et al 2006, Rebola, Lujan et al 2008, Simoes, Machado et al 2016, Kerkhofs, Canas et al 2018). While A 1 ARs mainly contribute in shaping short-term synaptic plasticity, A 2A ARs are more engaged in modulating long-term potentiation (d’Alcantara, Ledent et al 2001, de Mendoncca and Ribeiro 2001, Qi, van Aerde et al 2017, Lopes, Goncalves et al 2023). In light of this, adenosine is a neuromodulator that contributes to the precision of information processing mediated by a balanced activation of the inhibitory A1 and the excitatory A 2A ARs.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro electrophysiology in acute slices from the dorsal hippocampus, prefrontal cortex (PFC) and amygdala was performed as previously described [ 84 ]. Briefly, after sacrifice by cervical dislocation, the brain was quickly removed and submerged in ice-cold, oxygenated (95% O 2 , 5% CO 2 ) artificial cerebrospinal fluid (ACSF; in mM: 124.0 NaCl, 4.4 KCl, 1.0 Na 2 HPO 4 , 25.0 NaHCO 3 , 2.0 CaCl 2 , 1.0 MgCl 2 , 10.0 glucose).…”
Section: Methodsmentioning
confidence: 99%
“…The placement of stimulation and recording electrodes was done as described before [ 84 ]. In the hippocampus, the stimulating bipolar concentric electrode was placed in the proximal CA1 stratum radiatum for the stimulation of the Schaffer fibers and the recording electrode, filled with 4 M NaCl (2–5 MΩ resistance), was placed in the CA1 stratum radiatum targeting the distal dendrites of pyramidal neurons; in the amygdala, the bipolar concentric stimulation electrode and the recording electrode were placed in the lateral nuclei of the amygdala; in the PFC, the bipolar concentric stimulation electrode was placed in layer II/III and the recording electrode was placed in layer V. The stimulation was performed using either a Grass S44 or a Grass S48 square pulse stimulator (Grass Technologies, Carlow, Ireland) or a Digitimer DS3 stimulator (Digitimer LTD, Welwyn Garden City, UK), with rectangular pulses of 0.1 millisecond applied every 15–20 s. After amplification (ISO-80, World Precision Instruments, Hitchin, UK; or AxoPatch 200B amplifier, Axon Instruments, San Jose, CA, USA), the recordings were digitized (BNC-2110, National Instruments, Austin, TX, USA, or Digidata 1322A, Axon Instruments), averaged in groups of 3–4 and analyzed using WinLTP software [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is observed that adenosine modulates hippocampal LTP through activation of adenosine A1R mostly only in young animals than in adult animals and A2 receptors in synaptic plasticity are mostly observed in aged rather than young animals 105 . What's more, A1 receptors in synaptic plasticity are under tight repression by A2A receptor engagement, and A2AR could play a key role in dampening A1R during high‐frequency induction of hippocampal LTP 159 …”
Section: Neurological Mechanism Of Eatp In Depressionmentioning
confidence: 99%